The “Growing” Reality of the Neurological Complications of Global “Stem Cell Tourism” - Julian, Katie; Yuhasz, Nick; Hollingsworth, Ethan; Imitola, Jaime (Seminars in Neurology, 2018)
“Stem cell tourism” is defined as the unethical practice of offering unproven cellular preparations to patients suffering from various medical conditions. This phenomenon is rising in the field of neurology as patients are requesting information and opportunities for treatment with stem cells for incurable conditions such as multiple sclerosis and amyotrophic lateral sclerosis, despite their clinical research and experimental designation. Here, we review the recent trends in “stem cell tourism” in both the United States and abroad, and discuss the recent reports of neurological complications from these activities. Finally, we frame critical questions for the field of neurology regarding training in the ethical, legal, and societal issues of the global “stem cell tourism,” as well as suggest strategies to alleviate this problem. Although there are ongoing legitimate clinical trials with stem cells for neurological diseases, procedures offered by “stem cell clinics” cannot be defined as clinical research. They lack the experimental and state-of-the-art framework defined by peers and the FDA that focus on human research that safeguard the protection of human subjects against economical exploitation, unwanted side effects, and futility of unproven procedures. “Stem cell tourism” ultimately exploits therapeutic hope of patients and families with incurable neurological diseases and can put in danger the legitimacy of stem cell research as a whole. We posit that an improvement in education, regulation, legislation, and involvement of authorities in global health in neurology and neurosurgery is required.
Keywords: stem cell research; organoids; iPSCs; brain tumors; stem cell tourism; neural stem cells; ALS; MS